Improving the Educational Process Based on the Design and Development of Pedagogical Technology (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Pedagogical technology is a complex of systematic methods that allow the application of human potential and technical resources of the process of teaching and mastering knowledge in order to optimize educational forms, to determine their interaction. Technology refers to a process that results in a qualitative change in the subject as a result of the impact on the object by the subject. The technology is always intended to use the necessary tools and conditions to perform specific target actions directed at the object in a specific sequence.